Composite film and preparation method and application thereof

By constructing an electromagnetic dual gradient structure of the MXene film and an impedance matching layer, using the hollow structure HFO and the high conductivity MXene film, the electromagnetic wave reflection problem caused by the conductivity of the MXene material is solved, and efficient electromagnetic shielding and low reflection effects are achieved. Improves the mechanical properties of the material.

CN119264494APending Publication Date: 2025-01-07NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411581121.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing MXene materials have strong conductivity and lead to impedance mismatch, resulting in high reflection of electromagnetic waves, hindering the development of environmentally friendly EMI shielding materials.

Method used

A composite film consisting of a layered MXene film and an impedance matching layer is adopted. The impedance matching layer includes a multi-layer absorbing layer to gradually reduce the MXene content and increase the HFO content. The electromagnetic double gradient is constructed using the hollow structure HFO and the high conductivity MXene film. , reduce electromagnetic wave reflection and improve absorption efficiency.

Benefits of technology

It realizes efficient electromagnetic shielding performance and low electromagnetic wave reflection, reduces impedance mismatch, enhances microwave absorption capacity, improves EMI shielding efficiency, reduces material weight, and improves mechanical properties through bacterial cellulose.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264494A_ABST
    Figure CN119264494A_ABST
Patent Text Reader

Abstract

The invention provides a composite film as well as a preparation method and application thereof, and belongs to the field of polymer nano composite materials. The invention provides a composite film. The composite film comprises an MXene film and an impedance matching layer which are stacked in sequence, the impedance matching layer comprises absorption layers which are stacked in sequence; each absorption layer independently comprises cellulose, MXene dispersed in the cellulose and HFO dispersed in the cellulose; the HFO is of a hollow structure; in the direction from the MXene film to the impedance matching layer, in each absorption layer, the content of the MXene is gradually reduced, and the content of the HFO is gradually increased. Through the construction of electromagnetic double gradients, the reasonable arrangement of the MXene film and the impedance matching layer and the use of the hollow structure HFO, an absorption-reflection-reabsorption shielding mechanism is synergistically enhanced, the EMI shielding effectiveness is improved, impedance mismatch is effectively reduced, and the reflection ratio is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer nanocomposite materials, and in particular to a composite film and a preparation method and application thereof. Background Art

[0002] The 5G era has promoted the rapid development of electronic and electrical equipment. As the efficiency of electronic and electrical equipment increases, more electromagnetic interference (EMI) will be generated. In addition to causing electronic equipment to malfunction, electromagnetic interference will also destroy the stable magnetic field around human organs and endanger human health. It is urgent to study a high-performance electromagnetic interference shielding material with integrated multifunctionality.

[0003] MXene materials are considered as a promising EMI shielding material due to their rich surface functional groups, typical two-dimensional layered structure and ability to combine the superior conductivity of metals with the high chemical stability of carbon-based materials. However, the impedance mismatch caused by the superior conductivity of the material surface also means high reflection of electromagnetic waves, which may lead to secondary electromagnetic pollution and hinder the development of new environmentally friendly EMI shielding materials. Summary of the invention

[0004] The invention provides a composite film and a preparation method and application thereof. The composite film of the invention has high-efficiency electromagnetic shielding performance and low electromagnetic wave reflection.

[0005] The present invention provides a composite film, comprising a MXene film and an impedance matching layer stacked in sequence; the impedance matching layer comprises an absorption layer stacked in sequence; each absorption layer independently comprises cellulose, MXene dispersed in the cellulose, and HFO dispersed in the cellulose; the HFO is a hollow structure;

[0006] Along the direction from the MXene film to the impedance matching layer, in each absorption layer, the content of the MXene gradually decreases, and the content of the HFO gradually increases.

[0007] Preferably, the cellulose comprises bacterial cellulose and / or plant cellulose.

[0008] Preferably, the bacterial cellulose has a diameter of 50 to 100 nm and a length of 20 to 25 μm;

[0009] The plant cellulose has a diameter of 5 to 10 nm and a length of 1 to 3 μm.

[0010] Preferably, the MXene in each absorption layer and the MXene in the MXene film include a single few-layer Ti3C2T prepared by a fluoride salt method. x .

[0011] Preferably, the average particle size of the HFO is 350-400 nm, and the shell thickness is 10-15 nm.

[0012] Preferably, the mass ratio of cellulose to MXene in each absorption layer is independently 1:0-1, and the mass ratio of cellulose to HFO is independently 1:0-1.

[0013] Preferably, the impedance matching layer includes four layers of films stacked in sequence.

[0014] Preferably, the mass ratio of cellulose to MXene in the first film of the impedance matching layer is 1:0.15-0.4, and the mass ratio of cellulose to HFO is 1:0.1-0.35;

[0015] The mass ratio of cellulose to MXene in the second membrane is 1:0.1-0.2, and the mass ratio of cellulose to HFO is 1:0.3-0.4;

[0016] The mass ratio of cellulose to MXene in the third membrane is 1:0.05-0.1, and the mass ratio of cellulose to HFO is 1:0.4-0.45;

[0017] There is no MXene in the fourth membrane, and the mass ratio of cellulose to HFO is 1:0.5.

[0018] The present invention also provides a method for preparing the composite film described in the above technical solution, comprising the following steps:

[0019] According to the design, the dispersion liquid of each layer of membrane raw material in the composite thin film is filtered and dried in turn to obtain the composite thin film.

[0020] The present invention also provides the use of the composite film described in the above technical solution or the composite film prepared by the preparation method described in the above technical solution in the preparation of composite material films.

[0021] The HFO (Fe3O4) in the composite film of the present invention is a magnetic filler. The hollow structure of the HFO can reduce impedance mismatch and allow the incident electromagnetic waves to have numerous loss paths inside the composite film, thereby achieving a good shielding effect. The hollow structure of the HFO reduces the weight of the electromagnetic interference shielding material. In addition, the present invention controls the content of MXene in the absorption layer to construct an electrical gradient in the direction from the MXene film to the impedance matching layer, and controls the content of HFO to construct a magnetic gradient, so that the composite film has an electromagnetic double gradient. The electromagnetic double gradient allows electromagnetic waves to enter the composite film without generating too much reflection, thereby improving the electromagnetic shielding performance and reducing the electromagnetic wave reflection. The pure MXene bottom layer with high conductivity in the MXene film can effectively reflect and prevent residual electromagnetic waves from penetrating the composite film, ensuring a high electromagnetic shielding effectiveness value, and the electromagnetic waves reflected back to the impedance matching layer by the MXene film will continue to experience dielectric loss and magnetic loss attenuation, which improves the composite film's absorption value of electromagnetic waves, thereby improving the electromagnetic shielding performance and reducing electromagnetic wave reflection. Therefore, the present invention synergistically improves its microwave absorption in terms of magnetic loss, electrical loss and dielectric loss through the construction of electromagnetic dual gradients, the reasonable arrangement of MXene films and impedance matching layers, and the use of hollow structure HFO, strengthens the "absorption-reflection-reabsorption" shielding mechanism, improves EMI shielding effectiveness, effectively reduces impedance mismatch, and reduces reflectance.

[0022] Furthermore, the present invention uses bacterial cellulose as the matrix material of the absorption layer, which is environmentally friendly, non-toxic and renewable. It exists between and on the surface of the MXene layers, plays a supporting and connecting role, and improves the problem of poor mechanical properties of the composite film.

[0023] Furthermore, the single few-layer Ti3C2T prepared by the fluoride salt method x It has good dispersibility and electrical conductivity, and at the same time adds a large number of active oxygen-containing groups to its surface, which is beneficial to its surface modification.

[0024] The impedance matching layer prepared by the present invention exhibits both efficient electromagnetic shielding performance and low electromagnetic wave reflection characteristics. Due to the different chemical compositions and microscopic morphologies on both sides, the film also exhibits multifunctionality and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the structure of the composite film of the present invention;

[0026] Figure 2 is the SEM image of the composite film of Example 3;

[0027] Figure 3 This is a diagram of the mechanical properties of the composite film of Example 3;

[0028] Figure 4This is a graph showing the total electromagnetic shielding effectiveness of the composite film of Example 3;

[0029] Figure 5 This is a diagram of the absorption and reflection efficiency of the composite film of Example 3. DETAILED DESCRIPTION

[0030] The present invention provides a composite film, comprising a MXene film and an impedance matching layer stacked in sequence; the impedance matching layer comprises an absorption layer stacked in sequence; each absorption layer independently comprises cellulose, MXene dispersed in the cellulose and / or HFO dispersed in the cellulose; the HFO is a hollow structure;

[0031] In the direction from the MXene film to the impedance matching layer, in each absorption layer, the content of the MXene gradually decreases, and the content of the HFO gradually increases.

[0032] In the present invention, the composite film comprises a MXene film; the MXene in the MXene film preferably comprises a single few-layer Ti3C2T prepared by a fluoride salt method. x .

[0033] In the present invention, the composite film includes an impedance matching layer on the surface of the MXene film; the impedance matching layer includes absorption layers stacked in sequence; each absorption layer independently includes cellulose, MXene dispersed in the cellulose and / or HFO dispersed in the cellulose; the HFO is a hollow structure.

[0034] In the present invention, in the direction from the MXene film to the impedance matching layer, in each absorption layer, the content of the MXene gradually decreases, and the content of the HFO gradually increases. In the present invention, the content of the MXene can preferably be reduced to 0.

[0035] In the present invention, the mass ratio of cellulose to MXene in each absorption layer is preferably independently 1:0-1. In a specific embodiment of the present invention, the mass ratio of cellulose to MXene in each absorption layer may be independently 1:0, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1; the mass ratio of cellulose to HFO is preferably independently 1:0-1. In a specific embodiment of the present invention, the mass ratio of cellulose to HFO in each absorption layer may be independently 1:1, 1:0.9, 1:08, 1:0.7, 1:0.6, 1:0.5, 1:0.4, 1:0.3, 1:0.2, 1:0.1 or 1:0.

[0036] The composite film of the present invention preferably comprises four layers of film stacked in sequence; in the present invention, in each layer of the film, the total mass fraction of the MXene and HFO is preferably 50%:

[0037] In the present invention, the mass ratio of cellulose to MXene in the first layer of the impedance matching layer is preferably 1:0.15-0.4. In a specific embodiment of the present invention, the mass ratio of cellulose to MXene in the first layer of the membrane may be 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35 or 0.4; the mass ratio of cellulose to HFO is preferably 1:0.1-0.35. In a specific embodiment of the present invention, the mass ratio of cellulose to HFO in the first layer of the membrane may be 1:0.35, 1:0.3, 1:0.25, 1:0.2, 1:0.15 or 1:0.1.

[0038] The mass ratio of cellulose to MXene in the second layer of the membrane is preferably 1:0.1-0.2. In a specific embodiment of the present invention, the mass ratio of cellulose to MXene in the second layer of the membrane may be 1:0.1, 1:0.15 or 0.2. The mass ratio of cellulose to HFO is preferably 1:0.3-0.4. In a specific embodiment of the present invention, the mass ratio of cellulose to HFO in the second layer of the membrane may be 1:0.4, 1:0.35 or 1:0.3.

[0039] The mass ratio of cellulose to MXene in the third layer of the membrane is preferably 1:0.05-0.1. In a specific embodiment of the present invention, the mass ratio of cellulose to MXene in the third layer of the membrane may be 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09 or 1:0.1; the mass ratio of cellulose to HFO is 1:0.4-0.45. In a specific embodiment of the present invention, the mass ratio of cellulose to HFO in the third layer of the membrane may be 1:0.45, 1:0.44, 1:0.43, 1:0.42, 1:0.41 or 1:0.4.

[0040] The fourth layer of the film preferably contains no MXene; the mass ratio of cellulose to HFO is preferably 1:0.5.

[0041] In the present invention, the cellulose preferably includes bacterial cellulose and / or plant cellulose; the diameter of the bacterial cellulose is preferably 50-100 nm, and the length is preferably 20-25 μm; the diameter of the plant cellulose is preferably 5-10 nm, and the length is preferably 1-3 μm.

[0042] In the present invention, the MXene in the absorption layer preferably comprises a single few-layer Ti3C2T prepared by a fluoride salt method. x .

[0043] In the present invention, the HFO has a hollow structure.

[0044] In the present invention, the particle size of the HFO is preferably 350-400 nm, and the thickness of the shell is preferably 10-15 nm.

[0045] Figure 1 This is a schematic diagram of the structure of the composite film of the present invention: the four absorption layers serve as impedance matching layers to better allow electromagnetic waves to enter the composite film without generating too much reflection, and the highly conductive shielding layer is sufficient to prevent residual electromagnetic waves from penetrating the composite film, providing a strong guarantee for high-performance EMI shielding.

[0046] The present invention also provides a method for preparing the composite film described in the above technical solution, comprising the following steps:

[0047] According to the design, the dispersion liquid of each layer of membrane raw material in the composite thin film is filtered and dried in turn to obtain the composite thin film.

[0048] In the present invention, the filter membrane used for the suction filtration preferably includes a polyethersulfone filter membrane.

[0049] In the present invention, the filtration preferably further comprises: Stripping Then dry.

[0050] The present invention also provides the use of the composite film described in the above technical solution or the composite film prepared by the preparation method described in the above technical solution in the preparation of composite material films.

[0051] The composite film, preparation method and application thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0052] Example 1

[0053] (1) Preparation of dark green Ti3C2T x Single / few layer dispersion: 2g LiF was added to 40mL 9mol / L hydrochloric acid solution and stirred evenly; then 2g Ti3AlC2 powder was slowly added thereto and reacted at room temperature for 24h; after the reaction, the supernatant was washed with deionized water until the pH value was about 6, and then added to 40mL deionized water, and ultrasonically treated in an ice bath for 30min under the protection of inert gas; after centrifugation, the supernatant was taken to obtain a Ti3C2T3O3 dispersion with a concentration of 5mg / mL. x Mono / few-layer dispersions.

[0054] (2) Preparation of monodisperse HFO: 2 mmol FeCl3·6H2O, 4 mmol sodium citrate and 6 mmol urea were dissolved in 40 mL deionized water, and then 0.3 g polyacrylamide was added, stirred continuously until completely dissolved, transferred to a Teflon-lined stainless steel autoclave, heated to 200°C and maintained for 12 h. After cooling to room temperature, the black product was centrifuged, washed with deionized water and ethanol, and then dried under vacuum overnight to obtain HFO (Fe3O4) with an average particle size of 380 nm and a shell thickness of 12 nm.

[0055] (3) Preparation of BC aqueous dispersion: A strain of Acetobacter xylinum was selected and cultured in a culture medium having a pH value of 4.5. The culture medium consisted of 2.5% (w / v) glucose, 0.75% (w / v) yeast extract, 1% (w / v) tryptophan, 1% (w / v) disodium hydrogen phosphate and water. The culture medium was first sterilized at 121°C for 30 min and then statically incubated at 30°C for 36 h to produce a bacterial cellulose film with a thickness of about 1 mm. A small piece of bacterial cellulose film was immersed in water and the cells were broken by ultrasound to separate the bacterial cellulose nanofibers from the film to obtain a BC aqueous dispersion with a mass fraction of 0.8 wt%, wherein the bacterial cellulose had a diameter of 50 nm and a length of 20 μm.

[0056] (4) Conductive filler Ti3C2T x and magnetic filler HFO were dispersed in BC aqueous dispersion at different mass ratios, ultrasonically dispersed for 0.5h, and prepared by layer-by-layer vacuum filtration method:

[0057] Containing 100mgTi3C2T x The aqueous dispersion is first filtered onto a polyethersulfone filter membrane as a conductive layer, and then the absorption layer 1 is filtered, the mass ratio of BC (100 mg), MXene, and HFO in the aqueous dispersion is 1:0.4:0.1; the absorption layer 2, the mass ratio of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg):0.2:0.3; the absorption layer 3, the aqueous dispersion of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg):0.1:0.4; the absorption layer 4, the aqueous dispersion of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg):0:0.5; the obtained hydrogel is dried in a natural state, and is peeled off from the filter membrane to obtain an impedance matching layer (G-BMH) with an electromagnetic dual gradient structure.

[0058] The obtained film has a tensile strength of 100 MPa, an electromagnetic shielding effectiveness of 68 dB in the X-band (8.2-12.4 GHz), and a reflection effectiveness of 6.4 dB.

[0059] Example 2

[0060] (1) Preparation of dark green Ti3C2T x Single / few layer dispersion: 2g LiF was added to 40mL 9mol / L hydrochloric acid solution and stirred evenly; then 2g Ti3AlC2 powder was slowly added thereto and reacted at room temperature for 24h; after the reaction, the supernatant was washed with deionized water until the pH value was about 6, and then added to 40mL deionized water, and ultrasonically treated in an ice bath for 30min under the protection of inert gas; after centrifugation, the supernatant was taken to obtain a Ti3C2T3O3 dispersion with a concentration of 5mg / mL. x Mono / few-layer dispersions.

[0061] (2) Preparation of monodisperse HFO: 2mmol FeCl3·6H2O, 4mmol sodium citrate and 6mmol urea were dissolved in 40mL deionized water, and then 0.3g polyacrylamide was added, stirred continuously until completely dissolved, transferred to a Teflon-lined stainless steel autoclave, heated to 200°C and maintained for 12h. After cooling to room temperature, the black product was centrifuged, washed with deionized water and ethanol, and then dried under vacuum overnight to obtain HFO, the average particle size of which was 380nm and the shell thickness was 12nm.

[0062] (3) Preparation of BC aqueous dispersion: A strain of Acetobacter xylinum was selected and cultured in a culture medium having a pH value of 4.5. The culture medium consisted of 2.5% (w / v) glucose, 0.75% (w / v) yeast extract, 1% (w / v) tryptophan, 1% (w / v) disodium hydrogen phosphate and water. The culture medium was first sterilized at 121°C for 30 min and then statically incubated at 30°C for 36 h to produce a bacterial cellulose film with a thickness of about 1 mm. A small piece of bacterial cellulose film was immersed in water and the cells were broken by ultrasound to separate the bacterial cellulose nanofibers from the film to obtain a BC aqueous dispersion with a mass fraction of 0.8 wt%, wherein the bacterial cellulose had a diameter of 50 nm and a length of 20 μm.

[0063] (4) Conductive filler Ti3C2T x and magnetic filler HFO were dispersed in BC aqueous dispersion at different mass ratios, ultrasonically dispersed for 0.5h, and prepared by layer-by-layer vacuum filtration method:

[0064] Containing 100mgTi3C2T xThe aqueous dispersion is first filtered onto a polyethersulfone filter membrane as a conductive layer, and then the absorption layer 1 is filtered, the mass ratio of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg): 0.3: 0.2; the absorption layer 2, the mass ratio of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg): 0.2: 0.3; the absorption layer 3, the mass ratio of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg): 0.1: 0.4; the absorption layer 4, the mass ratio of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg): 0: 0.5; the obtained hydrogel is dried in a natural state, and is peeled off from the filter membrane to obtain an impedance matching layer (G-BMH) with an electromagnetic dual gradient structure.

[0065] The obtained film has a tensile strength of 108 MPa, an electromagnetic shielding effectiveness of 68 dB in the X-band (8.2-12.4 GHz), and a reflection effectiveness of 5.8 dB.

[0066] Example 3

[0067] (1) Preparation of dark green Ti3C2T x Single / few layer dispersion: 2g LiF was added to 40mL 9mol / L hydrochloric acid solution and stirred evenly; then 2g Ti3AlC2 powder was slowly added thereto and reacted at room temperature for 24h; after the reaction, the supernatant was washed with deionized water until the pH value was about 6, and then added to 40mL deionized water, and ultrasonically treated in an ice bath for 30min under the protection of inert gas; after centrifugation, the supernatant was taken to obtain a Ti3C2T3O3 dispersion with a concentration of 5mg / mL. x Mono / few-layer dispersions.

[0068] (2) Preparation of monodisperse HFO: 2mmol FeCl3·6H2O, 4mmol sodium citrate and 6mmol urea were dissolved in 40mL deionized water, and then 0.3g polyacrylamide was added, stirred continuously until completely dissolved, transferred to a Teflon-lined stainless steel autoclave, heated to 200°C and maintained for 12h. After cooling to room temperature, the black product was centrifuged, washed with deionized water and ethanol, and then dried under vacuum overnight to obtain HFO, the average particle size of which was 380nm and the shell thickness was 12nm.

[0069] (3) Preparation of BC aqueous dispersion: A strain of Acetobacter xylinum was selected and cultured in a culture medium having a pH value of 4.5. The culture medium consisted of 2.5% (w / v) glucose, 0.75% (w / v) yeast extract, 1% (w / v) tryptophan, 1% (w / v) disodium hydrogen phosphate and water. The culture medium was first sterilized at 121°C for 30 min and then statically incubated at 30°C for 36 h to produce a bacterial cellulose film with a thickness of about 1 mm. A small piece of bacterial cellulose film was immersed in water and the cells were broken by ultrasound to separate the bacterial cellulose nanofibers from the film to obtain a BC aqueous dispersion with a mass fraction of 0.8 wt%, wherein the bacterial cellulose had a diameter of 50 nm and a length of 20 μm.

[0070] (4) Conductive filler Ti3C2T x and magnetic filler HFO were dispersed in BC aqueous dispersion at different mass ratios, ultrasonically dispersed for 0.5h, and prepared by layer-by-layer vacuum filtration method:

[0071] Containing 100mgTi3C2T x The aqueous dispersion is first filtered onto a polyethersulfone filter membrane as a conductive layer, and then the absorption layer 1 is filtered, the mass ratio of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg): 0.15: 0.35; the absorption layer 2, the mass ratio of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg): 0.1: 0.4; the absorption layer 3, the mass ratio of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg): 0.05: 0.45; the absorption layer 4, the mass ratio of BC, MXene, and HFO in the aqueous dispersion is 1 (100 mg): 0: 0.5; the obtained hydrogel is dried in a natural state, and is peeled off from the filter membrane to obtain an impedance matching layer (G-BMH) with an electromagnetic dual gradient structure.

[0072] The obtained film has a tensile strength of 112 MPa, an electromagnetic shielding effectiveness of 68 dB in the X-band (8.2-12.4 GHz), and a reflection effectiveness of 5.1 dB.

[0073] Comparative Example 1

[0074] (1) Preparation of dark green Ti3C2T x Single / few layer dispersion: 2g LiF was added to 40mL 9mol / L hydrochloric acid solution and stirred evenly; then 2g Ti3AlC2 powder was slowly added thereto and reacted at room temperature for 24h; after the reaction, the supernatant was washed with deionized water until the pH value was about 6, and then added to 40mL deionized water, and ultrasonically treated in an ice bath for 30min under the protection of inert gas; after centrifugation, the supernatant was taken to obtain a Ti3C2T3O3 dispersion with a concentration of 5mg / mL. x Mono / few-layer dispersions.

[0075] (2) Preparation of monodisperse HFO: 2mmol FeCl3·6H2O, 4mmol sodium citrate and 6mmol urea were dissolved in 40mL deionized water, and then 0.3g polyacrylamide was added, stirred continuously until completely dissolved, transferred to a Teflon-lined stainless steel autoclave, heated to 200°C and maintained for 12h. After cooling to room temperature, the black product was centrifuged, washed with deionized water and ethanol, and then dried under vacuum overnight to obtain HFO, the average particle size of which was 380nm and the shell thickness was 12nm.

[0076] (3) Preparation of BC aqueous dispersion: A strain of Acetobacter xylinum was selected and cultured in a culture medium having a pH value of 4.5. The culture medium consisted of 2.5% (w / v) glucose, 0.75% (w / v) yeast extract, 1% (w / v) tryptophan, 1% (w / v) disodium hydrogen phosphate and water. The culture medium was first sterilized at 121°C for 30 min and then statically incubated at 30°C for 36 h to produce a bacterial cellulose film with a thickness of about 1 mm. A small piece of bacterial cellulose film was immersed in water and the cells were broken by ultrasound to separate the bacterial cellulose nanofibers from the film to obtain a BC aqueous dispersion with a mass fraction of 0.8 wt%, wherein the bacterial cellulose had a diameter of 50 nm and a length of 20 μm.

[0077] (4) Conductive filler Ti3C2T x and magnetic filler HFO dispersed in BC aqueous dispersion (conductive filler Ti3C2T x , the total amount of magnetic fillers HFO and BC is consistent with the total amount in Example 3), ultrasonic dispersion is performed for 0.5h, and the mixed dispersion is filtered on a polyethersulfone filter membrane by vacuum filtration. The obtained hydrogel is dried in a natural state and peeled off from the filter membrane to obtain an impedance matching layer (H-BMH) with a uniform structure.

[0078] The obtained film has a tensile strength of 50 MPa, an electromagnetic shielding effectiveness of 40 dB in the X-band (8.2-12.4 GHz), and a reflection effectiveness of 7.2 dB.

[0079] Table 1 Film parameters of Examples 1 to 3 and Comparative Example 1

[0080] Tensile Strength Shielding effectiveness Reflection performance Example 1 100MPa 68dB 6.4dB Example 2 108MPa 68dB 5.8dB Example 3 112MPa 68dB 5.1dB Comparative Example 1 50MPa 40dB 7.2dB

[0081] Table 1 shows that the introduction of bacterial cellulose provides a guarantee for the enhancement of the mechanical properties of MXene films. This is because there are a large number of terminals on the surface of the MXene sheets, which can combine with bacterial cellulose fibers through strong electrostatic attraction and hydrogen bonding, and the strong hydrogen bonding interaction between the layers of the multilayer film is conducive to promoting the transfer and dissipation of loads between the layers, thereby improving the mechanical properties. The construction of electromagnetic dual gradients significantly improves its electromagnetic shielding effectiveness, which is better than the uniformly structured H-BMH film prepared in the comparative example, and the reflection efficiency remains at a low level.

[0082] Figure 2 This is the SEM image of the composite film of Example 3.

[0083] Depend on Figure 2 It can be seen that the connection between adjacent layers is closely integrated, which can greatly improve the mechanical properties. The Fe element shows a light and dark gradient opposite to the Ti element, which further verifies the authenticity of the electromagnetic dual gradient structure.

[0084] Figure 3 This is a diagram of the mechanical properties of the composite film of Example 3.

[0085] Depend on Figure 3 It can be seen that the tensile strength of the obtained film can reach 112MPa, which improves the problem of poor mechanical properties of single MXene film.

[0086] Figure 4 This is a diagram of the total electromagnetic shielding effectiveness of the composite film of Example 3.

[0087] Figure 4 It was verified that when the composite membrane has an electromagnetic dual gradient, the composite membrane has excellent electromagnetic shielding performance.

[0088] Figure 5 This is a diagram of the absorption and reflection efficiency of the composite film of Example 3.

[0089] Figure 5 This once again proves the rationality of the hollow structure and the electromagnetic dual gradient structure. The electric / magnetic double loss is conducive to enhancing the "absorption-reflection-reabsorption" shielding mode, which is of great significance for reducing secondary electromagnetic pollution.

[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite film, characterized in that: It comprises a MXene film and an impedance matching layer stacked in sequence; the impedance matching layer comprises an absorption layer stacked in sequence; each absorption layer independently comprises cellulose, MXene dispersed in the cellulose and HFO dispersed in the cellulose; the HFO is a hollow structure; Along the direction from the MXene film to the impedance matching layer, in each absorption layer, the content of the MXene gradually decreases, and the content of the HFO gradually increases.

2. The composite film according to claim 1, characterized in that The cellulose includes bacterial cellulose and / or plant cellulose.

3. The composite film according to claim 2, characterized in that: The bacterial cellulose has a diameter of 50 to 100 nm and a length of 20 to 25 μm; The plant cellulose has a diameter of 5 to 10 nm and a length of 1 to 3 μm.

4. The composite film according to claim 1, characterized in that The MXene in each absorbing layer and the MXene in the MXene film include a single few-layer Ti3C2T prepared by a fluoride salt method. x .

5. The composite film according to claim 1, characterized in that The average particle size of the HFO is 350-400 nm, and the shell thickness is 10-15 nm.

6. The composite film according to claim 1, 4 or 5, characterized in that: The mass ratio of cellulose to MXene in each absorption layer is independently 1:0-1, and the mass ratio of cellulose to HFO is independently 1:0-1.

7. The composite film according to claim 1, 4 or 5, characterized in that: The impedance matching layer includes four films stacked in sequence.

8. The composite film according to claim 7, characterized in that: The mass ratio of cellulose to MXene in the first film of the impedance matching layer is 1:0.15-0.4, and the mass ratio of cellulose to HFO is 1:0.1-0.35; The mass ratio of cellulose to MXene in the second membrane is 1:0.1-0.2, and the mass ratio of cellulose to HFO is 1:0.3-0.4; The mass ratio of cellulose to MXene in the third membrane is 1:0.05-0.1, and the mass ratio of cellulose to HFO is 1:0.4-0.45; There is no MXene in the fourth membrane, and the mass ratio of cellulose to HFO is 1:0.

5.

9. The method for preparing the composite film according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the design, the dispersion liquid of each layer of membrane raw material in the composite thin film is filtered and dried in turn to obtain the composite thin film.

10. Use of the composite film according to any one of claims 1 to 8 or the composite film prepared by the preparation method according to claim 9 in the preparation of composite material films.